Analisis Penggunaan Metode Tilawati dalam Pengembangan Kemampuan Membaca Al-Qur’an Siswa SDN 1 Sejati di Kabupaten Wonogiri - Vina Eka Putri; Sanjaka Yekti (Ta’dib : Jurnal Pendidikan Islam, 2026)
This study aims to analyze the implementation of the Tilawati method in improving Qur’an reading skills and students’ understanding of basic tajwid at Sejati 1 State Elementary School, Wonogiri. The research subjects consisted of 30 students from grades 3 to 5 and 4 teachers. Using a descriptive qualitative approach, data were collected through participant observation using a rubric covering reading fluency, tajwid, and intonation, as well as in-depth interviews and documentation. The data were then analyzed through triangulation. The findings indicate that the implementation of the Tilawati method, with gradual emphasis and melodic practice using the rost tone, improved students’ confidence in independent Qur’an recitation and enhanced their tajwid accuracy. A total of 70% of students showed improvement in reading fluency. The main challenge was the variation in students’ initial abilities, which required differentiated instruction. This study contributes to the practice of Qur’an teaching in elementary schools by offering a locally contextualized approach to strengthening students’ religious character.